The Sociological Meaning of The Nineteen Daily Meetings of Baha'i Religions in Medan - Qiftiah, Salsabilla Raudhatul; Harahap, Suheri; Muary, Rholand (International Journal of Cultural and Social Science, 2023)
This study discusses the Sociological Meaning of the Nineteen Daily Meetings of the Baha'i Religion in Medan City. Basically, humans need religion in their lives, to serve as a principle of life for both life in this world and in the hereafter. One of the religions in Indonesia, namely the Baha'i Religion, the Baha'i Religion entered Indonesia in 1878, in the Baha'i religion there is a tradition of nineteen daily meetings, where this tradition contains meaning in every celebration. The theory used in this study uses the theory of symbolic interactionism, the essence of symbolic interactionism itself is an interaction or communication using symbols that are given meaning. This study uses qualitative methods with data collection techniques such as observation, interviews, and documentation. This research resulted in an understanding of the sociological meaning of the nineteen daily meetings with 5 Baha'i religious leaders in the city of Medan. The results obtained are: Blumer's conclusion rests on three main premises, namely: (1) humans act based on the meanings that exist in something for them; (2) the meaning is obtained from the results of social interactions carried out with fellow adherents of the Baha'i religion; (3) these meanings are perfected when the process of social interaction is taking place.